Resiniferatoxin: The Evolution of the "Molecular Scalpel" for Chronic Pain Relief - Dorothy Cimino Brown (MDPI AG, 2016)
Control of chronic pain is frequently inadequate or can be associated with debilitating side effects. Ablation of certain nociceptive neurons, while retaining all other sensory modalities and motor function, represents a new therapeutic approach to controlling severe pain while avoiding off-target side effects. transient receptor potential cation channel subfamily V member 1 (TRPV1) is a calcium permeable nonselective cation channel expressed on the peripheral and central terminals of small-diameter sensory neurons. Highly selective chemoablation of TRPV1-containing peripheral nerve endings, or the entire TRPV1-expressing neuron itself, can be used to control chronic pain. Administration of the potent TRPV1 agonist resiniferatoxin (RTX) to neuronal perikarya or nerve terminals induces calcium cytotoxicity and selective lesioning of the TRPV1-expressing nociceptive primary afferent population. This selective neuroablation has been coined "molecular neurosurgery" and has the advantage of sparing motor, proprioceptive, and other somatosensory functions that are so important for coordinated movement, performing activities of daily living, and maintaining quality of life. This review examines the mechanisms and preclinical data underlying the therapeutic use of RTX and examples of such use for the management of chronic pain in clinical veterinary and human pain states.